Pharmacokinetics, Pharmacodynamics, Safety and Immunogenicity of CMAB807, a New Denosumab Biosimilar, in Healthy Chinese Subjects - Chen, Hanjing; Chen, Weili; Yuan, Fei; Guo, Qingcheng; Zhang, Xunmin; Wang, Chenguang; Li, Xuening (Frontiers in Pharmacology, 2022)
Objective: Pharmacokinetics (PK), pharmacodynamics (PD), safety and immunogenicity studies were conducted to evaluate the bioequivalence of CMAB807, a biosimilar to denosumab (Prolia®), which is the only approved RANKL inhibitor for the treatment of osteoporosis. Methods: In this randomized, double-blind, single-dose phase I study, 132 healthy Chinese male subjects received a subcutaneous injection of 60 mg of CMAB807 or denosumab at a 1:1 ratio. The PK, PD, safety and immunogenicity results were assessed prior to and up to 126 days after administration. Results: The PK profiles of CMAB807 and denosumab were similar. The geometric mean ratios of the maximum concentration (Cmax), AUC0-t, and AUCo-∞ were 102.41%, 104.15% and 103.89%, respectively, and the 90% confidence interval was observed to be within 80.00-125.00%, which indicated the bioequivalence of CMAB807 and denosumab. The PD profiles of the two groups were also comparable. The production of the C-terminal cross-linking telopeptide of type I collagen (CTX1) was inhibited by up to 85% for 10 days, and this inhibition was sustained for up to 126 days in both the CMAB807 and denosumab groups. No subjects in the CMAB807 group, 3 subjects in the denosumab group before administration, and 2 subjects in the denosumab group after administration were positive for anti-drug antibody (ADA). Adverse events (AEs) were observed in 98.5% of subjects in both groups. The most common AE recorded was increased parathyroid hormone (PTH) levels, with incidences of 92.4% and 95.5% in the CMAB807 and denosumab groups, respectively. No clinically meaningful differences were observed in safety and immunogenicity between CMAB807 and denosumab. Conclusion: CMAB807 represents a new potential new treatment option for patients with osteoporosis.